Răspuns:
Explicație pas cu pas:
a. f(x)=2x+1
∩OX, y=0⇒ 2x+1=0, x=[tex]-\frac{1}{2}[/tex] A([tex]-\frac{1}{2}[/tex],0)
∩OY, x=0⇒ y=0+1=1 B(0,1)
g(x)=2x
∩OX, y=0⇒ x=0, C(0,0)
∩OY, x=0⇒y=0, D(0,0)
Pentru ca avem 0 si 0
alegem 2 puncte
g(1)=2 C(1,2)
g(2)=4 D(2,4)
h(x)=2x-3
∩OX, y=0⇒ 2x-3=0, x=[tex]\frac{3}{2}[/tex] E([tex]\frac{3}{2}[/tex],0)
∩OY, x=0 ⇒ y=0-3=-3 F(0,-3)
b. f(x)=x+2
∩OX, y=0 ⇒x+2=0 x=-2 A(-2,0)
∩OY, x=0⇒ y=2 B(0,2)
g(x)=-x
C(0,0) D(0,0)
g(1)=-1 C(1,-1)
g(2)=-2 D(2,-2)
h(x)=-x-1
∩OX, y=0⇒ -x-1=0
x=-1 E(-1,0)
∩OY, x=0 ⇒ y=-1 F(0,1)
Pentru fiecare subpunct pui punctele aflate pe grafic